Alcatraz Versus the Shattered Lens : Alcatraz Versus The Evil Librarians #4 - Sanderson, Brandon (New York : Scholastic Press, 2010)
When a hero is needed to save the doomed kingdom of Mokia from the evil Librarians, thirteen-year-old Alcatraz Smedry, whose family talents include getting lost and breaking things, answers the call.
Keywords: Fantasy; Heroes -- Fiction; Librarians -- Fiction; Humorous fiction